Is celiac Disease common in patients with vitiligo? - Seyhan, Muammer; Kandi, Basak; Akbulut, Handan; Selimoglu, Mukadder Ayse; Karincaoglu, Melih (Aves, 2011)
[Abstract Not Available]
Keywords: Manifestations